The Living with Asthma Study - Hughes, Mary (Asthma Society of Ireland, 2014)
Ireland has the fourth highest incidence of asthma in the world (GINA 2004, 2012, Masoli et al. 2004). It is estimated that 14.7% of the population, or 470,000 Irish people have asthma, including 20% of Irish children, making it the most common chronic disease in childhood and the most common respiratory illness in Ireland (Asthma Society of Ireland 2014, Central Statistics Office 2008). Around 29% of people with asthma miss school or work because of it; adults are absent from work an average of 12 days and children are absent from school on average 10 days per year (Manning et al. 2007). There are more than 5,000 admissions per year to hospital for asthma treatment. The average cost of a hospital admission for asthma costs €2,737 (Health Service Executive 2009). The impact of asthma on people’s lives has been well established. The recent REALISE survey found that a poor level of control persists among people with asthma, even though they rate themselves to be well controlled (Price et al. 2014). Symptoms and exacerbations of symptoms are frequent and this is not regarded by people as problematic, unlike their healthcare providers. This suggests that people are willing to put up with a level of symptoms which may influence their quality of life.
PUBLISHED